1984
DOI: 10.1021/jo00177a015
|View full text |Cite
|
Sign up to set email alerts
|

Rotational selectivity in cyclobutene ring openings. Model studies directed toward a synthesis of verrucarin A

Abstract: 3.26 g of 26; 95% recovery) showed a resonance (6 3.68) only for methanesulfonyl chloride (26). Treatment of the aqueous phase with benzylthiuronium chloride gave neither benzylthiuronium methanesulfinate nor benzylthiuronium methanesulfonate (absence of methanesulfinic acid (24) and methanesulfonic Attempted Reaction of S-Methyl Methanesulfonothioate (12) with Activated Zinc at 0 "C. The experimental procedure described above for zinc and methanesulfonyl chloride (26) at 0 "C for 1 h was repeated except thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…One of these enantiomers was also available by enzymatic oxidation of diol 3a 15. Diesters and monoesters 7 – 8 were prepared from 1 either as racemates1d,8,16,17 or – for (+)‐8 – as the nonracemate 14a,18. In the case of 7c an alternative route from 1,3,5,7‐cyclooctatetraene has been proposed 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these enantiomers was also available by enzymatic oxidation of diol 3a 15. Diesters and monoesters 7 – 8 were prepared from 1 either as racemates1d,8,16,17 or – for (+)‐8 – as the nonracemate 14a,18. In the case of 7c an alternative route from 1,3,5,7‐cyclooctatetraene has been proposed 19.…”
Section: Introductionmentioning
confidence: 99%
“…This would increase the effective bulk of this substituent, resulting in its preferential outward rotation, in contrast to reactions carried out in CCl 4 or CH 2 ClCH 2 Cl. Influence of secondary orbital interactions was also envisioned 17. Over the years it became evident that numerous results could not be interpreted only in terms of steric effects, and theoretical works on these ring openings by Houk’s group22 showed that orbital interactions within the transition state tend to favor outward rotation in the case of π‐donor groups and inward rotation in the case of π‐acceptor substituents.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative, electrocyclic ring-opening strategy has been illustrated by Trost, where a cis cyclobutene ring opening approach was used for the total synthesis of verrucarin A. [11] Starting from macrocyclic compound 8, a 2:1 mixture of the two E,Z-isomers (9 and 10) was obtained (Scheme 3, eq (a)). Later, Wallace described the electrocyclic ring opening of cis cyclobutenecarbaldehyde 11 (Scheme 3, eq (b)).…”
Section: Reviews Ascwiley-vchdementioning
confidence: 99%
“…I2.13-Epoxy-4a-hydronytrichothec-9-en-15-yl Acetate (23 (13) (14)); 1.73 (s, CH3(16)); 2.03 (m. CH2 (7), CH2(8)); 2.49 (m, H-C(3)); 2.81, 3.10 (AB, J = 4, CH2 (13) …”
Section: 13-epoxy-4-oxo-3cc-[(tetrahydro-2 H-pyranyl)oxyjtrichothementioning
confidence: 99%
“…This result suggests that the macrolidic part possesses a cytotoxic activity independent of the epoxybearing trichothecene moiety. The cytotoxic activities of macrocyclic trichothecene mode1 compounds which do not possess the trichothecene moiety support this hypothesis [23]. However, with the data available at present, it is too early to draw final conclusions for the structural requirements for the biological activity of trichothecene mycotoxins.…”
mentioning
confidence: 93%